1289. Pravibismane is a Potent, Broad Spectrum Anti-Infective Small Molecule that Rapidly Disrupts Bacterial Bioenergetics and Halts Bacterial Growth. (31st December 2020) - Baker, Brett
Abstract: Background: The rise in resistance to existing antimicrobials has prompted a need for the development of novel antibiotics. Microbion has identified a novel compound, pravibismane, with potent broad spectrum anti-infective and anti-biofilm activity. Methods: Here we used a variety of assays, including Bacterial Cytological Profiling (BCP), to analyze pravibismane in E.coli to gain insight into its likely mechanism of action (MOA). The BCP profile of pravibismane suggested it rapidly shut down cell growth, potentially by turning off cellular gene or protein expression. This was confirmed using a plasmid based GFP induction assay in E.coli tolC that showed pravibismane strongly reduced expression of GFP. The kinetics, reversibility and MOA of pravibismane was further characterized by using time-lapse microscopy, wash out experiments and measurements of both membrane potential and relative intracellular ATP levels. Results: We found that pravibismane acts rapidly (within 30 mins) to completely halt cell growth rather than causing immediate cell lysis such as that observed with non-specific cell damaging agents bleach or detergent. Inhibitor wash out experiments in which cells were exposed to pravibismane for 2 hours, washed to remove the compound, and then observed using time-lapse microscopy revealed that the effect of pravibismane is reversible and that cells recovered 8-12 hrs after removing the compound. Wash out experiments with an E.coli tolC strain carrying a plasmid with an IPTG inducible GFP demonstrated that transcription and translation ultimately resumed in most cells after washout. The bioenergetics of the membrane was measured using DiBAC 4(5), a membrane potential sensitive dye which can enter depolarized cells, which revealed that pravibismane caused depolarization of the membrane within 30 mins of exposure in a concentration dependent manner. Finally, a luciferase assay determined pravibismane reduced ATP levels (resulting in decreased luminescence) within 15 mins of exposure in a concentration dependent manner unlike antibiotic controls that had modest or no effect on luminescence. Conclusion: Our results suggest that pravibismane acts rapidly to disrupt cellular bioenergetics, resulting in the immediate cessation of cell growth and protein expression. Disclosures: Brett Baker, M.Sc., D.C., Microbion Corporation (Board Member, Employee)